Obstructive sleep apnea in children: update on the recognition, treatment and management of persistent disease. (2nd April 2016) - Tan, Hui-Leng; Kheirandish-Gozal, Leila; Gozal, David
ABSTRACT: Adenotonsillectomy (AT) is the recommended first-line treatment for pediatric obstructive sleep apnea (OSA) in children with adenotonsillar hypertrophy. It is now clearly established that AT results in improvement in the severity of OSA in most children. However, a significant number of OSA children undergoing AT exhibit residual persistent OSA post-surgery. Patients at increased risk of persistent OSA include those with severe disease at initial review, older or obese patients, children with underlying asthma or allergic rhinitis, and those who have concurrent underlying medical conditions, such as Trisomy 21, craniofacial syndromes or cerebral palsy. Here, we aim to highlight recent research findings into those who have persistent OSA disease, and suggest a practical approach to the management of these children.